Crime in the 2016 Presidential Election: a new era? - Hill, Joshua B. (American journal of criminal justice, 2018)
Issues pertaining to crime and criminal justice have long been part of presidential campaigns. Voters want to know how candidates plan to solve the problem of crime and keep them safe. In turn, candidates respond to voters’ concerns and describe their crime control ideas in hopes of increasing voter support. In doing so, they often rely on symbolic statements that provide little detail but make people “feel good”. This study analyzes the criminal justice rhetoric used by the three major presidential candidates in the 2016 election cycle to determine what issues they discussed and how often. The analysis also examines if candidates relied on symbolic statements, and how the issues were debated between the candidates. The findings show that the issues discussed were somewhat different than in previous years, and that the candidates relied on symbolic statements about crime – a change from the previous election cycle. Additionally, the candidates used crime control as a way to reach out to voters in their own political party, suggesting an interesting shift in how issues of criminal justice are being approached within elections.